PERFORMANCE EVALUATION TECHNIQUES FOR THE NUCLEAR GRADE MAIN FEED-WATER CONTROL VALVE - LIU QingMin; GAO ZhaoJie; LIN Feng; ZHANG QiangSheng; WU Xin (Jixie qiangdu)
A performance evaluation technology was studied for the seismic performance evaluation of nuclear safety Class II main feed-water control valve based on the ASME Code and finite element analysis platform（ Femap + NX Nastran）.First,we proposed an analysis model for the vertical control valve,and the risk assessment and improvement methods for the structural characteristics of vertical control valve were studied.Then we conducted a numerical model for a control valve and compared the simulation data with those obtained from experimental test.These two showed good agreement.Finally,the seismic performance evaluation of a main feed-water control valve was performed under the combination of the seismic load and design load.The simulated relative error of inner stresses at typical site is less than 5% compared with that obtained by using empirical formula.The simulated data shows that the designed valve fulfills the design requirement for its first order frequency is bigger than 33 HZ,and the maximum stresses are within the allowable range under various load cases.